Evaluation of the reheating behavior of the cooling slope cast A356 and A380 aluminum alloys - Acar, Serhat; Acici, Nazim; Guler, Kerem Altug (IOP Publishing Ltd, 2019)
A356 and A380 alloys are two well-known hypoeutectic Al-Si casting alloys in the non-ferrous casting industry and drew significant attention for semi-solid applications. The cooling slope casting method for producing materials with non-dendritic microstructure is one of the simplest liquid route techniques. In the beginning, microstructural differences of both alloys produced with 30 degrees and 60 degrees tilt angles were examined. It was observed that the angle change has a limited effect on A380 and it is almost non-effective for A356 as-cast structures. The samples were then subjected to the reheating processes for different times and the effects were investigated by measuring the average shape factor and the grain size values. In addition to the natural grain growth, it is understood that the changes in the eutectic are also effective on the properties. The rapid solidification of the melted eutectic by quenching the reheated samples modified the eutectic structure and improved the hardness. On the other hand, grain growth reduces hardness naturally. Additionally, it was observed that the increase in sphericity was supported by the liquid phase formation and it was determined that A356 alloy was more sensitive to reheating and formed larger grains than A380 alloy for the same reheating periods.
Keywords: cooling slope casting; semi-solid reheating; A356 alloy; A380 alloy; MICROSTRUCTURAL EVOLUTION; AL-ALLOY; OPTIMIZATION; Materials Science